2016
DOI: 10.1177/1747493015625645
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrolysin dose-dependently improves neurological outcome in rats after acute stroke: A prospective, randomized, blinded, and placebo-controlled study

Abstract: Collectively, these data on Cerebrolysin efficacy demonstrate the feasibility of a preclinical study setup following a randomized, placebo-controlled, and blinded design with a clinical relevant treatment scheme. Cerebrolysin at doses of ≥ 2.5 ml/kg improved functional outcome and at a dose of 5 ml/kg reduced infarct volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
2
19
0
2
Order By: Relevance
“…Using the same prospective, randomized, blinded, placebo-controlled protocol, the doseresponse effects of Cerebrolysin on functional outcomes were also shown in a rat model of stroke. 59 Furthermore, our previous study found that delayed treatment with Cerebrolysin (2.5 ml/kg, starting 24 hours after injury and then daily for 28 days) improves cognitive function at least up to 3 months in a rat model of mTBI. 60 Collectively, these findings suggest that Cerebrolysin has the potential to treat acute and subacute brain injuries.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Using the same prospective, randomized, blinded, placebo-controlled protocol, the doseresponse effects of Cerebrolysin on functional outcomes were also shown in a rat model of stroke. 59 Furthermore, our previous study found that delayed treatment with Cerebrolysin (2.5 ml/kg, starting 24 hours after injury and then daily for 28 days) improves cognitive function at least up to 3 months in a rat model of mTBI. 60 Collectively, these findings suggest that Cerebrolysin has the potential to treat acute and subacute brain injuries.…”
Section: Discussionmentioning
confidence: 96%
“…Cerebrolysin were selected based on our previous studies in rats with experimental stroke 59 or mTBI. 60 The study design, surgeries, preparation of study medication, treatment, data collection, and analysis were each performed by different and independent members of the Henry Ford Hospital.…”
mentioning
confidence: 99%
“…The drug doses were chosen based on our previous studies in TBI 18 and stroke. 17 Treatment with study drug was initiated 4 hours after injury and was administered intraperitoneally once daily for 10 consecutive days. Study medication was prepared by a designated investigator (who was not involved in any other part of this study) according to animal body weight, 1 day prior to treatment based on the randomization scheme.…”
Section: Animal Groups and Treatmentmentioning
confidence: 99%
“…12 Besides these protective effects, cerebrolysin promotes neurogenesis in animal models of AD, 13 stroke, 14,15 and TBI. 16,17 Cerebrolysin increases neuronal survival in the hippocampus, preserves axonal integrity in the striatum, enhances vascular patency and integrity after moderate TBI, 18 and reduces APP levels and astrogliosis in rats after mTBI. 16 Collectively, these multiple beneficial effects resulting from cerebrolysin treatment may in concert contribute to improvement of neurological outcome after brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Под влиянием препарата активируются нейрогенез, синаптогенез и олигодендрогенез [55]. Введение Церебролизина при фокаль-ной ишемии приводит к снижению объема поврежденной мозговой ткани [56,57], что способствует формированию менее выраженной постинсультной симптоматики.…”
Section: применение церебролизинаunclassified